The conundrum of Nazi law: an historiographical challenge to the Anglo-American jurisprudential representation of the Nazi past - Lavis, Simon (2015)
The question of whether Nazi law was valid law has been at the background of jurisprudential discourse since the Hart-Fuller debate in the 1950s. The enduring focus of that discourse on the validity question – the conditions of validity for law – and the separability question – the nature of the relationship between law and morality – has consigned the Third Reich to a specific jurisprudential role as a limit case for positivism and natural law. This dissertation elucidates and interrogates that role, using recent empirical and theoretical historical research to challenge its basis and assert the substantive relevance of the Nazi past for present legal theoretical concerns.